2018
DOI: 10.1177/0145445517751435
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parental Acceptability and Preference for Behavioral Interventions for Feeding Problems

Abstract: The present study evaluates the treatment acceptability and preference for behavioral interventions for feeding problems with parents of children with Autism Spectrum Disorder and other developmental disabilities. The impact of behavioral severity on acceptability and preference was also evaluated by comparing results of parents who responded with respect to a vignette of a child with food refusal with those who responded to a vignette of a child with food selectivity. Overall, parents rated differential reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…This study contributed to the literature by assessing social validity of a potentially invasive behavior‐analytic feeding intervention. Previous research has suggested that when given a choice, parents select less invasive interventions (e.g., Vazquez, Fryling, & Hernandez, ). This could be problematic in the treatment of pediatric feeding disorders, as more invasive interventions (e.g., escape extinction, physical guidance) may be necessary to treat food refusal.…”
Section: Discussionmentioning
confidence: 99%
“…This study contributed to the literature by assessing social validity of a potentially invasive behavior‐analytic feeding intervention. Previous research has suggested that when given a choice, parents select less invasive interventions (e.g., Vazquez, Fryling, & Hernandez, ). This could be problematic in the treatment of pediatric feeding disorders, as more invasive interventions (e.g., escape extinction, physical guidance) may be necessary to treat food refusal.…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of existing literature on the treatment of food selectivity and refusal has shown that escape extinction is an effective, and often necessary, intervention (Ahearn et al, ; Bachmeyer, ; Cooper et al, ). However, treatments involving extinction may result in unwanted side effects such as extinction bursts, making continued implementation of treatment difficult and negatively impacting social acceptance of extinction as a treatment component (Vazquez et al, ). An examination of 10 cases in which severe food refusal was treated with escape extinction revealed a burst of IMB during the initiation of extinction procedures for 40% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although escape extinction is an empirically validated procedure to reduce food refusal and increase food intake, it may be associated with several unwanted side effects similar to those observed when extinction procedures are implemented with other topographies of problem behavior (e.g., aggression and crying). A recent study by Vazquez, Fryling, and Hernández () suggests that parents may find the use of escape extinction procedures unacceptable in the treatment of food refusal. The most common side effect of extinction procedures reported in the applied literature is an extinction burst (Lerman, Iwata, & Wallace, ; Lerman & Iwata, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach has the potential to be invasive and may be inappropriate for some children (Sharp et al, 2010;Williams et al, 2010). For example, a study by Vazques et al (2019) asked parents to rate the acceptability of feeding treatments when given a hypothetical example. These parents rated escape extinction as the least acceptable.…”
mentioning
confidence: 99%